A New LiNH4SO4 Crystal with an Isotropic Point - Stadnyk, V.Yo.; Romanyuk, M.O.; Brezvin, R.S. (Ukrainian Journal of Physics, 2012)
LiNH4SO4 crystals of α-modification were grown up, and the spectral dependences of their refractive indices and birefringence are studied. The intersection of ni(λ) curves is found, which testifies to the inversion of birefringence sign (Δny = 0) at the light wavelength λ0 ≈ 683 nm at room temperature. For higher temperatures, this point shifts toward the short-wave spectral range. The temperature dependence of the angle between the optical axes is examined, and the change of the optic axial plane at the transition into the isotropic state is demonstrated.